2018
DOI: 10.1021/acs.analchem.7b04586
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution High Kinetic Energy Ion Mobility Spectrometer Based on a Low-Discrimination Tristate Ion Shutter

Abstract: High kinetic energy ion mobility spectrometry (HiKE-IMS) allows for sensitive trace gas analysis within seconds, mitigating many disadvantages of standard ion mobility spectrometers through operation at reduced pressure and high electric field strengths. However, these advantages usually come at the cost of reduced resolving power, ranging from a maximum of 75 down to 50 at a reduced field strength of 120 Td for the original device. In this work, we present an extended theory for HiKE-IMS resolving power and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 33 publications
3
131
0
Order By: Relevance
“…While the B–N gate has been the workhorse of commercial and research instruments for many years, there are well-known limitations associated with the short injection times required to push the resolving power beyond 100. 21 , 53 55 To the best of our knowledge, all of the ultrahigh-resolution systems reported for DT-IMS have used a field switching gate rather than a B–N gate.…”
Section: Resultsmentioning
confidence: 99%
“…While the B–N gate has been the workhorse of commercial and research instruments for many years, there are well-known limitations associated with the short injection times required to push the resolving power beyond 100. 21 , 53 55 To the best of our knowledge, all of the ultrahigh-resolution systems reported for DT-IMS have used a field switching gate rather than a B–N gate.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the HiKE‐IMS setup was previously provided by Kirk et al 24 The operating parameters used in this work are presented in Table 1. To identify individual ion species associated with signals in the ion mobility spectrum, the HiKE‐IMS‐MS coupling described in a previous work 21 is used.…”
Section: Methodsmentioning
confidence: 99%
“…This agrees well with the experimental results of Tabrizchi et al [1] and An et al [14], who both observed a quadratic increase in ion current with increasing applied voltage. Third, in HiKE-IMS, where the reduced field strength E/N is an experimental parameter used to control the ion chemistry, the pressure inside the device is inversely proportional to the length at a constant available voltage [15]. Thus, reducing the length and increasing the pressure in HiKE-IMS would result in a quadratically increasing ion current at the same reduced field strength E/N.…”
Section: Analytical Modelmentioning
confidence: 99%